PEMBUATAN DAN PENGUJIAN ANEMOMETER KAWAT PANAS TEMPERATUR KONSTAN UNTUK PENGUKURAN KECEPATAN UDARA PADA ALIRAN SWIRLING - Diasta, I N; Santoso, Arianto; Sutikno, Priyono; Dinata, Uyung G. S (Mesin, 1998)
To overcome the difficulties in calibrating a hot wire anemometer the equation E2 = A+BU0.45, as the reference equation in making hot wire anemometer, was changed to U = (1/ B (E2-A))2.22 to produce linear calibration curve. To realize this idea then an electronic circuit was designed with IC AD 534 and AD 538 as the main components. IThe hot-wire anemometer was made based upon the above principles then used to measure velocity components of swirling flow, which has two components of velocity, i.e.: axial (normal) velocity and tangential velocity. In measurement of swirling flow the probe-X was used to measure axial velocity and tangential velocity simultaneously. Magnitude and direction of swirling ï¬ow were determined from those velocity components.